Análise ergonômica da prática do paratletismo de lançamentos: rendimento esportivo e prevenção de lesões musculoesqueléticas relacionadas ao esporte - Pinto, Evelyne Tenório Gomes da Silva (2018)
The aim of this dissertation is to elaborate guidelines for joint optimization in the practice of parathetism, that is, to contribute to the formulation of strategies for the prevention of musculoskeletal injuries and to improve the performance of the paratheleting athletes of dart and disc throwing. Paralympic sport has great potential, but it has been marked by high prevalence and incidence of injuries, which can compromise athletes' health and performance. A long and complex chain of factors interact in this phenomenon, and may promote imbalance in the relationship between the athlete's ability to dissipate, generate and transfer mechanical energy and the amount of stress imposed on the musculoskeletal system during the performance of sports activities. This study aims to understand these factors and their relation to the athletics modality of launches, for individuals with spinal cord injuries, of the functional class F55. The research had as methodological approach the Ergonomic Analysis of the Work. Interaction and observation techniques, conversational action scripts, verbalizations, photographic records and videos were used. The study of the practice of dart and disc launches has evidenced the adoption of different operative modes by athletes in training and competition contexts, some of which are pathogenic in terms of musculoskeletal injuries, and inhibitors of better yields. The operative modes are related to aspects of work organization (planning, monitoring, cadence, goals, etc..) of training, with the technology (launching chair, implement) used in the training and with the characteristics of the athlete (functional class etc.). There was a lack of systematized breaks during the training sessions and the minimum requirement for the technical team to improve the movements of the implements during training, the performance of training outside the prescribed periodization of the group, the absence of follow-up of the athletes, by the technical team, and the lack of use of musculoskeletal injuries prevention monitoring instruments, as well as income. Other items were also evidenced, such as the use of launching chairs, handcrafted, without adequately taking into account athletes' anthropometric data, their characteristics, their functional class, their practice and actual use - activity itself - nor the comfort, safety, portability and modularity criteria. All of these associated factors contribute to the development and / or worsening of musculoskeletal injuries in postpartum patients, as well as their income, in their entirety. At the end of this research it was possible to understand the modality studied, within its peculiarities and contexts, thus enabling the elaboration of recommendations for improvement to sports practice, from the perspective of joint optimization. It is therefore recommended that athletes perform an anthropometric study, for the development of launching chairs, the production of launching chairs for the training and competition contexts, considering criteria of safety, comfort, performance, functional class and modality the launch of a formal break at each launch during the performance of the training, a systematic correction of the movements of the athletes, by the technical team, among others.